DUALITY IN SPACES OF FUNCTIONS PLURIHARMONIC IN THE UNIT BALL IN C^n - Gapoyan, N.T. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
Banach spaces h_∞ (), h_0 () and h^1(η) of functions, pluriharmonic in the unit ball in C^n, depending on weight function and weighting measure η are introduced. The question we consider is: for given we find a finite positive Borel measure η on [0,1) such that h^1(η)^* hicksim h_∞ () and h_0 ()^* hicksim h^1(η) .